2004
DOI: 10.1590/s0006-87052004000200011
|View full text |Cite
|
Sign up to set email alerts
|

Fate of 15N-urea applied to wheat-soybean succession crop

Abstract: The wheat crop in São Paulo State, Brazil, is fertilized with N, P and K. The rate of applied N (0 to 120 kg.ha -1 ) depends on the previous grown crop and the irrigation possibility. The response of wheat to rates and time of N application and the fate of N applied to irrigated wheat were studied during two years. Residual N recovery by soybean grown after the wheat was also studied. The maximum grain productivity was obtained with 92 kg.ha -1 of N. The efficiency of 15 N-urea utilization ranged from 52% to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
3
6
0
2
Order By: Relevance
“…These mean air temperatures observed in winter in SP (Boaretto et al, 2004) were close to the mean temperatures recorded in the summer experiment with maize. In the first maize crop (2009/10), volatilization losses were highest in treatments with urea application in the morning and the afternoon with 13.2 and 12.2 % of applied N, respectively.…”
Section: Cumulative Nh 3 -N Lossessupporting
confidence: 80%
See 1 more Smart Citation
“…These mean air temperatures observed in winter in SP (Boaretto et al, 2004) were close to the mean temperatures recorded in the summer experiment with maize. In the first maize crop (2009/10), volatilization losses were highest in treatments with urea application in the morning and the afternoon with 13.2 and 12.2 % of applied N, respectively.…”
Section: Cumulative Nh 3 -N Lossessupporting
confidence: 80%
“…In an experiment with wheat in the winter in São Paulo State, Boaretto et al (2004) found N volatilization losses ranging from 5 to 12 % of N applied as urea, higher than those recorded in the winter in the South-Central region of Paraná. Possibly, the lower volatilization losses recorded in south-central of Paraná were related to lower daily temperatures (~14 °C), than in the Southeast region (~21 °C).…”
Section: Cumulative Nh 3 -N Lossesmentioning
confidence: 83%
“…As already mentioned, in other regions and other experiments the N leaching component was always of minor importance. Reichardt et al (2009) also working with coffee found N leaching of 2.3% of the total N applied, Gava et al (2006) for corn and Boaretto et al (2004) for wheat reported losses of 1%, and Quiñones et al (2005 and for citrus under controlled environment found only 0.1% of N losses.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors have reported low recovery (about 3.5% of the N) by the second crop after sunn hemp cover crop (Silva et al, 2006) or hairy vetch (Vicia villosa Roth) plowed into the soil (Seo et al, 2006). Low recovery of residual N has also been observed for inorganic fertilizer sources: less than 3% of the N derived from fertilizers was taken up by soybeans (Glicine max (L) Merril) (Boaretto et al, 2004), maize (Silva et al, 2006), Seo et al (2006) or sugarcane (Saccharum spp.) (Basanta et al, 2003).…”
Section: ------------------------------------------------------------mentioning
confidence: 94%